1997
DOI: 10.1090/s0002-9947-97-01617-6
|View full text |Cite
|
Sign up to set email alerts
|

The conjugacy problem for groups of alternating prime tame links is polynomial-time

Abstract: Abstract. An alternating projection of a prime link can to used to produce a group presentation (of the link group under free product with the infinite cyclic group) with some useful peculiarities, including small cancellation conditions. In this presentation, conjugacy diagrams are shown to have the form of a tiling of squares in the Euclidean plane in one of a limited number of shapes. An argument based on the shape of the link projection is used to show that the tiling requires no more square tiles than a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…A trivial tangle is a pair (B 3 , t), where B 3 is a 3-ball and t is a union of two arcs properly embedded in B 3 which is parallel to a union of two mutually disjoint arcs in ∂B 3 . By a rational tangle, we mean a trivial tangle (B 3 , t) which is endowed with a homeomorphism from (∂B 3 , ∂t) to (S 2 , P ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A trivial tangle is a pair (B 3 , t), where B 3 is a 3-ball and t is a union of two arcs properly embedded in B 3 which is parallel to a union of two mutually disjoint arcs in ∂B 3 . By a rational tangle, we mean a trivial tangle (B 3 , t) which is endowed with a homeomorphism from (∂B 3 , ∂t) to (S 2 , P ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proved by Weinbaum [16] and Appel and Schupp [1] that the word and conjugacy problems for prime alternating link groups are solvable, by using small cancellation theory (see also [3] and references in it). Moreover, it was also shown by Sela [15] and Préaux [12] that the word and conjugacy problems for any link group are solvable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that in the proof for the non-peripherality of short arcs we actually solved the conjugacy problem. We could also have shown that these elements were nonperipheral by using Johnsgard's solution to the conjugacy problem [Joh97]: using Johnsgard's algorithm, the fact that the peripheral complex contains the geodesic completion of l m , and the periodicity of the peripheral complex, it is straight-forward to show that a geodesic word in the augmented Dehn presentation is conjugate to a peripheral element l a m b if and only if it embeds as a geodesic path from (0, k) to (an + k − b, an + b), for some integer k. It is easy to see that two words in (5) and ( 6) are not of this form. We can use a similar argument for Wirtinger loops.…”
Section: 3mentioning
confidence: 98%
“…The key tool for solving the question is small cancellation theory, applied to two-generator and one-relator presentations of 2-bridge link groups. We note that it has been proved by Weinbaum [32] and Appel and Schupp [5] that the word and conjugacy problems for prime alternating link groups are solvable, by using small cancellation theory (see also [10] and references in it). Moreover, it was shown by Sela [24] and Préaux [21] that the word and conjugacy problems for any link group are solvable.…”
Section: Introductionmentioning
confidence: 95%